2020
DOI: 10.1124/jpet.120.000163
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of Diuresis and Natriuresis by Cannabinoids: Evidence for Inhibition of Na+-K+-ATPase in Mouse Kidney Thick Ascending Limb Tubules

Abstract: The endocannabinoid, anandamide (AEA), stimulates cannabinoid receptors (CBR) and is enriched in the kidney, especially the renal medulla. AEA infused into the renal outer medulla of mice stimulates urine flow rate and salt excretion. Here we show that these effects are blocked by the CBR Type I (CB1) inverse agonist, rimonabant. Immunohistochemical analysis demonstrated the presence of CB1 in thick ascending limb (TAL) tubules. Western immunoblotting demonstrated the presence of CB1 (52 KDa) in the cortex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…CB1R may also modulate the Ang II pressor effect by its action on sodium and water balance. As described earlier, CB1R may be involved in the regulation of salt and water balance (46,79,122,(127)(128)(129)(130). Furthermore, Ang II type 1 receptors (AT1) are largely expressed within the kidney.…”
Section: The Role Of the Endocannabinoid System On Blood Pressure Regulationmentioning
confidence: 92%
See 4 more Smart Citations
“…CB1R may also modulate the Ang II pressor effect by its action on sodium and water balance. As described earlier, CB1R may be involved in the regulation of salt and water balance (46,79,122,(127)(128)(129)(130). Furthermore, Ang II type 1 receptors (AT1) are largely expressed within the kidney.…”
Section: The Role Of the Endocannabinoid System On Blood Pressure Regulationmentioning
confidence: 92%
“…However, recent data shown that a peripheral modulation could also be involved (46,79,(127)(128)(129). As mentioned above, several studies confirmed that tubular cells express the main components of ECS, including CB1R and possibly CB2R as well as the enzymes for biosynthesis and degradation of their ligands (74,130). However, not only the physiological role of CB1R in tubular cells, but also the mechanism responsible for an aquaretic and/or diuretic effect of ECS, remain controversial.…”
Section: The Role Of the Endocannabinoid System In Tubular Cellsmentioning
confidence: 96%
See 3 more Smart Citations